AKTIVITAS ANTIKANKER SENYAWA ASILFLOROGLUSINOL DARI BIJI Melicope incana TERHADAP SEL KANKER PAYUDARA MCF-7 - Mulyadi Tanjung (Universitas Islam Bandung, 2021)
Melicope incana is one of the plant species that belongs to family Rutaceae. Melicope produces phenolic compounds, including alkaloids, acylphloroglucinol, flavonoids, and coumarins. This study aims to isolate the acyl phloroglucinol derivatives found in M. incana seeds. Extraction of acylphloroglucinol derivatives with methanol using the maceration method at room temperature. Separation and purification using a combination of gravity column chromatography, and radial chromatography. Two acylphloroglucinol compounds have been isolated, namely 3'-geranyl-2',4',6'-trihydroxy acetophenone (1) and 3'-isoprenyl-2',4',6'-trihydroxy acetophenone (2). The structure of the two compounds was determined based on UV, IR, 1D, and 2D NMR spectroscopic analysis. Anticancer activity of compounds 1-2 against breast cancer cells MCF-7 showed IC50 values of 48.98 and 4.30 µg /mL, respectively.